Effects of Endoscopic Sinus Surgery and Nasal Surgery in Patients with Obstructive Sleep Apnea. (31st March 2014) - Yalamanchali, Sreeya; Cipta, Stephanie; Waxman, Jonathan; Pott, Thomas; Joseph, Ninos; Friedman, Michael
Abstract : Objectives: To evaluate the impact of combined nasal surgery and endoscopic sinus surgery on the objective measurements of obstructive sleep apnea (OSA) and sleep architecture by comparing polysomnographic data before and after combined surgery in patients with OSA. Study Design: Case series with chart review. Setting: A single clinical site. Subjects and Methods: Patients with OSA and chronic rhinosinusitis who underwent combined nasal surgery and endoscopic sinus surgery and preoperative and postoperative polysomnography were identified. Patient charts were reviewed and preoperative and postoperative body mass index, apnea‐hypopnea index (AHI), mean and minimum oxygen saturation, sleep efficiency, and sleep staging were compared. Results: Fifty‐six patients were included in our study. Patients were divided into 3 groups on the basis of the severity of OSA: those with mild OSA (n = 9), those with moderate OSA (n = 23), and those with severe OSA (n = 24). After combined nasal and sinus surgery, the mean AHI significantly decreased from 33.5 ± 22.0 to 29.4 ± 20.8 ( P =. 009) in our overall population. Specifically, AHI improved significantly in patients with moderate OSA (from 22.3 ± 4.8 to 20.7 ± 8.2, P =. 023) and severe OSA (from 52.3 ± 21.4 to 43.6 ± 23.9, P =. 034), while patients with mild OSA did not have significant changes in AHI. Successful surgical procedures were achieved in only 2 of 56 patients. Conclusion: Although combined nasal and sinus surgery may slightly improve AHI in a certain group of patients, it does not cure OSA or have a significant clinical impact.